MECHANISMS OF THE INHIBITION OF CHEMOTAXIS BY PHOSPHONATE ESTERS - Ward, Peter A. (The Rockefeller University Press, 1967)
Studies in the time course of the response of rabbit polymorphonuclear leukocytes (PMN's) to the complement-associated chemotactic factor have revealed that the response is virtually complete by 60 min with less than 15% additionally responding cells thereafter. Phosphonate esters with a well defined capacity to inhibit serine esterases have been used to study the cell-associated enzymes of the rabbit PMN required for the chemotactic response. Two types of inhibition of the cell response to the chemotactic factor have been found: (a) cell-dependent inhibition occurring as a result of pretreatment of PMN's with phosphonate esters; and (b) chemotactic factor-dependent inhibition demonstrated only when the phosphonate ester is present during the chemotactic response. Differences were found in these two modes of inhibition caused by various phosphonates, in terms of their time course of inhibition, in the dose response curves, and in the structure-activity relationships. It has been conclusively demonstrated that the phosphonate esters have no direct inhibitory effect on the chemotactic factor. This has been shown by retention of activity of the chemotactic factor following incubation with phosphonate esters and subsequent removal by dialysis. In addition, the activity of the chemotactic factor and its physical-chemical characteristics in density gradient ultracentrifugation were unaltered in the continued presence of a potent phosphonate inhibitor of chemotaxis. The uptake of the dye trypan blue was studied in cells treated with phosphonate in such a manner to induce cell-dependent inhibition of chemotaxis. Even when 84% cell-dependent inhibition of chemotaxis occurred, no uptake of the dye by leukocytes was found. Thus, phosphonate-induced inhibition of cell responsiveness in chemotaxis was not associated with generalized cell damage as defined by exclusion of the dye. It is concluded that cell-dependent inhibition is due to the presence of a cell-bound esterase which is already activated and thus susceptible to inhibition by phosphonate esters before contact of the cell with the chemotactic factor. The second type of inhibition, chemotactic factor-dependent inhibition, is considered due to a cell-bound esterase which becomes susceptible to inhibition by phosphonate esters only after contact of the PMN with the chemotactic factor. It is postulated that the chemotactic factor activates this phosphonate-resistant precursor making it susceptible to the inhibitory action of the phosphonate ester.